Interface Carbon Content and its Influence on Carburization of Steel in Bimetallic Castings - Suchoń, J.; Kondracki, M. (Archives of Foundry Engineering, 2026)
Modern materials engineering is increasingly moving away from monolithic structures in favor of bimetal components. Layered castings combining steel and cast iron provide an excellent response to the conflicting operational requirements that machine parts must meet. Combining the high ductility and strength of steel with the exceptional abrasion resistance and vibration damping properties of cast iron allows for the creation of components that are both durable and crack-resistant. The key to success in this technology is achieving a permanent diffusion bond at the interface between the two phases, which requires precise control of the thermal and physicochemical parameters of the casting process. This paper presents the impact of the difference in carbon content between the joined layers on diffusion efficiency and, consequently, joint quality.